Effect of Antiplatelet Therapy on Acute Respiratory Distress Syndrome and Mortality in Critically Ill Patients: A Meta-Analysis. - Lijun Wang; Heng Li; Xiaofei Gu; Zhen Wang; Su Liu; Liyong Chen (PLoS ONE)
Background Antiplatelet agents are commonly used for cardiovascular diseases, but their pleiotropic effects in critically ill patients are controversial. We therefore performed a meta-analysis of cohort studies to investigate the effect of antiplatelet therapy in the critically ill. Methods Nine cohort studies, retrieved from PubMed and Embase before November 2015, involving 14,612 critically ill patients and 4765 cases of antiplatelet users, were meta-analysed. The main outcome was hospital or 30-day mortality. Secondary outcome was acute respiratory distress syndrome (ARDS) or acute lung injury (ALI). Random- or fixed-effect models were taken for quantitative synthesis of the data. Results Antiplatelet therapy was associated with decreased mortality (odds ratio (OR) 0.61; 95% confidence interval (CI), 0.52-0.71; I2 = 0%; P <0. 001) and ARDS/ALI (OR 0.64; 95% CI, 0.50-0.82; I2 = 0%; P <0. 001). In every stratum of subgroups, similar findings on mortality reduction were consistently observed in critically ill patients. Conclusions Antiplatelet therapy is associated with reduced mortality and lower incidence of ARDS/ALI in critically ill patients, particularly those with predisposing conditions such as high-risk surgery, trauma, pneumonia, and sepsis. However, it remains unclear whether similar findings can be observed in the unselected and broad population with critical illness.